Design and development Centrifugal Atomization machine for metal powder production – part 1 - Rosmaini Ismail (Universiti Malaysia Perlis, 2008)
Atomization is one of the processes for making the powder metal for powder metallurgy process. Atomization actually is the process where the molten metal was disintegrated into small droplets and rapidly solidified before the drops come into contact with each other or with solid surface. In atomization, there are various type processes such as water atomization, gas atomization, centrifugal atomization and others. All these processes have their own process and applications. For water atomization used the high pressure water to break up the powder. For gases atomization used high pressure gas. Usually use nitrogen and argon gases. For centrifugal use the high speed rotating disk to break up the molten metal become a particle. The diameter of the particle for this process is depending on the high speed rotating disc. To choose the appropriate machine to develop, need to produce some of concept design. From the concept design, the suitable machine will choose based on the criteria and the advantage and limitation of each machine. Also about the parameter was needed. From design concept also will know the process flow of the process of each machine. CATIA software was use to create a design in 3D and 2D for fabrication process. Lastly fabrication process is used the equipment in lab such as welding, drilling, and others to produce the machine structure.